Kentucky lawyer - Swinford, Mac (University Press of Kentucky, 2008)
Presenting the most humorous, enlightening, and touching moments of a remarkable fifty-year career, Kentucky Lawyer provides an authoritative and enjoyable portrayal of the legal profession. Mac Swinford, a legend of the Kentucky bar and bench, tackles topics ranging from the importance of amicus curiae to the court's encounters with Santa Claus.